Reducing motion-correction-induced variability in (82)rubidium myocardial blood-flow quantification - Poitrasson-Rivière, Alexis (J Nucl Cardiol, 2019)
BACKGROUND. Clinical use of myocardial blood flow (MBF) and flow reserve (MFR) is increasing. Motion correction is necessary to obtain accurate results but can introduce variability when performed manually. We sought to reduce that variability with an automated motion-correction algorithm. METHODS. A blinded randomized controlled trial of two technologists was performed on the motion correction of 100 dynamic (82)Rb patient studies comparing manual motion correction with manual review and adjustment of automated motion correction. Inter-rater variability between technologists for MBF and MFR was the primary outcome with comparison made by analysis of the limits of agreement. Processing time was the secondary outcome. RESULTS. Limits of agreements between the two technologists decreased significantly for both MBF and MFR, going from [−0.22, 0.22] mL/min/g and [−0.31, 0.36] to [−0.12, 0.15] mL/min/g and [−0.15, 0.18], respectively (both P<.002). In addition, the average time spent on motion correcting decreased by 1 min per study from 5:21 to 4:21 min (P=.001). CONCLUSIONS. In this randomized controlled trial, the use of automated motion correction significantly decreased inter-user variability and reduced processing time.